Peningkatan Literasi BPJS Ketenagakerjaan Bukan Penerima Upah (BPU) pada UMKM Kecamatan Sepatan Timur Tangerang - Herlina Herlina; Lia Ira Sahara; Dina Aulia (Perhimpunan Sarjana Ekonomi dan Bisnis, 2026)
East Sepatan District has significant potential for MSMEs as economic drivers, but they are vulnerable to occupational risks due to a lack of social safety nets. This Community Service (PKM) activity aims to improve literacy regarding the BPJS Ketenagakerjaan Non-Wage Recipients (BPU) among MSMEs in the region. Observations revealed that 90% of business owners had not yet participated in the Old Age Security (JHT) program, and 30% had inactive membership due to delinquent contributions. The methods used were interactive outreach and direct counseling regarding early protection and retirement financial planning. The results of the activity demonstrated an increase in partners' understanding of the importance of active participation via the JMO application, accident insurance benefits, and JHT savings management. Through this program, MSMEs in East Sepatan can operate their businesses with a sense of security.